The Effect of Cocoa Leaf Extract (Dendrophthoe pentandra (L.) Miq.) on The Growth of Shigella dysenteriae and Salmonella typhi - Della Mahda Yunita; Joko Waluyo; Siti Murdiyah (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2019)
Cocoa parasite leaves (Dendrophthoe pentandra (L.) Miq) belong to parasitic plants against hosts which are potentially used as traditional medicinal ingredients. However, the efficacy of cocoa parasite leaves is still not widely known by the public. One of the properties from cacao parasitic leaves is able to treat mild diseases such as smallpox, hookworm, flu, cough and diarrhea as well as being able to be used as a treatment for serious diseases such as tumors and cancer. The bacteria causing infection generally come from gram negative bacteria, namely Shigella dysenteriae and Salmonella typhi which refer to enteropathogenic bacteria causing infection to the host. The existing controls still use antibiotic drugs that are used less procedurally and causing bacteria more resistant. Cocoa parasite leaf extract contains active compounds in the form of alkaloids and saponins which play a role in inhibiting bacterial growth. This study aims to determine the effective concentration on the effect of cocoa parasite leaf extract to the growth of Shigella dysenteriae and Salmonella typhi bacteria. The research method was by using diffusion so that by using wells with 5 repetitions. The concentration used was 8%, 10%, 12%, 14%, 16%. Data were analyzed by using ANOVA analysis to determine the effective concentration on the effect of extracts to the inhibition of bacterial growth. The significant values were indicated at 0,000 against Shigella dysenteriae and 0.042 bacteria against Salmonella typhi (<0,05). The data revealed that cocoa parasite leaf extract has the potential to inhibit the growth of Shigella dysenteriae and Salmonella typhi bacteria.